Concept As A Fundamental Category In Linguocultural Studies (Texas Journal of Philology, Culture and History, 2024)
This article examines the semantic features of social protection terminology, focusing on homonymy and polysemantic relations in English and Uzbek. Using a comparative linguistic approach, the study identifies key terms that exhibit multiple meanings or interpretations in both languages. By analyzing these features, the research highlights challenges in translation and cross-cultural communication, emphasizing the importance of context in understanding and standardizing terminology. Practical recommendations for improving accuracy in translation and bilingual communication are provided. This study contributes to the field of applied linguistics by offering a deeper understanding of semantic complexity in multilingual contexts